Understanding the potential for efficient triplet harvesting with hot excitons. (23rd April 2019) - Northey, T.; Keane, T.; Eng, J.; Penfold, T. J.
Abstract : Excited state energy transfer in disordered systems has attracted significant attention owing to the importance of this phenomenon in both artificial and natural systems that operate in electronically excited states. Abstract : Excited state energy transfer in disordered systems has attracted significant attention owing to the importance of this phenomenon in both artificial and natural systems that operate in electronically excited states. Of particular interest, especially in the context of organic electronics, is the dynamics of triplet excited states. Due to their weak coupling to the singlet manifold they can often act as low energy trapping sites and are therefore detrimental to device performance. Alternatively, by virtue of their long lifetime they can lead to enhanced diffusion lengths important for organic photovoltaics (OPV). Herein, we explore the triplet energy transfer mechanism from dichlorobenzene to thioxanthone in methanol solution. We rationalise previous experimental observations as arising from preferential population transfer into the lowest triplet state rather than the higher lying triplet state that is closer in energy. The reason for this is a delicate balance between the electronic coupling, reorganisation energy and the energy gap involved. The present results provide the understanding to potentially develop a hot exciton mechanism in materials for organic light emitting diodes (OLED) to achieve higher device efficiencies.